Improving Students' Understanding Of Prevention And Eradication Of Illegal Drug Use And Abuse - Azwar, Azwar; Dhika, Veron (Jurnal Masyarakat Mengabdi, 2025)
Drug abuse poses a significant threat to the younger generation. National Narcotics Agency (2023) data indicates 312,000 users among students. This community service initiative aims to enhance the understanding and preventive capacity of students at Mercubaktijaya Padang University regarding the dangers of drugs through socialization of the P4GN program (Prevention and Eradication of Drug Abuse and Illicit Trafficking), supporting the realization of a BERSINAR Campus (Drug-Free Campus). The method utilized an educational intervention based on interactive lectures and participatory discussions, involving 150 students. Effectiveness was evaluated using a one-group pretest-posttest design with standardized questionnaires, analyzed statistically using a paired sample t-test. Results indicated a significant increase in knowledge (p<0.05). The proportion of participants with "Excellent" understanding rose from 15% to 68%. Furthermore, 90% of participants reported increased awareness of legal risks, and 85% expressed commitment to actively engage in prevention efforts within the campus environment. In conclusion, structured P4GN socialization proved effective in enhancing student literacy and fostering critical attitudes. This activity contributes to strengthening the prevention pillar at the community level. For sustainability, the establishment of a university-level P4GN task force and the integration of this material into student programs are recommended.